Applying Information Gain to Explore Factors Affecting Small-Incision Lenticule Extraction: A Multicenter Retrospective Study - Liang, Shuang; Ji, Shufan; Liu, Xiao; Chen, Min; Lei, Yulin; Hou, Jie; Li, Mengdi; Zou, Haohan; Peng, Yusu; Ma, Zhixing; Liu, Yuanyuan; Jhanji, Vishal; et al. (Frontiers in Medicine, 2022)
Purpose: This retrospective study aimed to identify the key factors influencing postoperative refraction after small-incision lenticule extraction (SMILE) using information gain. Methods: This study comprised 2350 eyes of 1200 patients who underwent SMILE using a Visumax 500-kHz femtosecond laser (Carl Zeiss Meditec AG) in three ophthalmic centers: Tianjin Eye Hospital (center A), Jinan Mingshui Eye Hospital (center B), and Qingdao Eye Hospital (center C). Anterior segment features, including corneal curvature and central corneal thickness (CCT), were obtained from Pentacam HR (Oculus, Wetzlar, Germany). Information gain was calculated to analyze the importance of features affecting postoperative refraction. Results: Preoperative and postoperative mean spherical equivalent (SE) refraction were -5.00 (-6.13, -3.88) D and 0.00 (-0.25, 0.13) D, respectively. None of the patients lost more than two lines of corrected distance visual acuity. The safety index was 1.32±0.24, 1.03±0.08, and 1.13±0.16 in centers A, B, and C, respectively. The efficacy index was 1.31±0.25, 1.02±0.08, and 1.13±0.17 in centers A, B, and C, respectively. At least 95% of the eyes were within ±1.00 D of the attempted correction. Postoperative refraction was related to preoperative spherical diopter refraction(r=0.369, p<0.001), preoperative SE(r=0.364, p<0.001), maximum lenticule thickness(r=–0.311, p<0.001), preoperative uncorrected distance visual acuity(r=0.164, p<0.001), residual stromal thickness (r=0.139, p<0.001), preoperative mean anterior corneal curvature (r=–0.127, p<0.001), preoperative flattest anterior corneal curvature(r=–0.122, p<0.001), nomogram(r=-0.100, p<0.001) and preoperative CCT(r=–0.058, p=0.005). Conclusions: SMILE was considered a safe and effective procedure for correcting myopia. Based on information gain, postoperative refraction was influenced by preoperative mean anterior corneal curvature, CCT, refraction, and residual stromal thickness.